If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 2 = 27x Reorder the terms: 2 + 9x = 27x Solving 2 + 9x = 27x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27x' to each side of the equation. 2 + 9x + -27x = 27x + -27x Combine like terms: 9x + -27x = -18x 2 + -18x = 27x + -27x Combine like terms: 27x + -27x = 0 2 + -18x = 0 Add '-2' to each side of the equation. 2 + -2 + -18x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -18x = 0 + -2 -18x = 0 + -2 Combine like terms: 0 + -2 = -2 -18x = -2 Divide each side by '-18'. x = 0.1111111111 Simplifying x = 0.1111111111
| 5.7(x-1)=-0.3+42.3 | | -3y-2=-2y | | -7x^3*8x^2= | | 9x^2+24x=9 | | 5m^2=112+8m | | p^2+3p^3-3p-1=0 | | 11-x+3=3n+3n | | G(t)=t+5 | | 2(v-5)+7v=4 | | 2x+8=360 | | -8n= | | 10x-6x=25-25 | | 62=9g | | 53=9g | | 44=9g | | 35=9g | | 26=9g | | 17=9g | | 4x+10(x+2)=60 | | X^2-5=3x+5 | | 8=9g | | 5y=-3x+14.50 | | 5r-1=19whatisr | | 10-7y=10 | | (x+2y)(x+5y)= | | 4(2x-3)=x+7 | | 8x-12=x+7 | | 4t^2+-9t=9 | | X^2-5x+6=2x-4 | | x^2-63+2x=0 | | 600x=800x(x-.75) | | 5(12-3x)-9x=4(3-2x) |